China's Offensive in Europe - Le Corre, Philippe, 1964 or 1965-; Sepulchre, Alain (Book collections on Project MUSE., 2016)
For years China's international investment interests focused on a search for natural resources in Africa, Asia, and Latin America. Recently, China's focus has shifted to Europe in fields as diverse as real estate, energy, hospitality, transportation, and heavy industry. Chinese foreign investment is expected to grow throughout Europe in years to come. The financial crisis and fall of the euro are helping Chinese companies create a new partnership within the European Union, working to expand China's power through finance and infrastructure. China's Offensive in Europe studies the trends, sectors, and target countries of Chinese investments in Europe. It also takes a look at European perceptions' of China - a country with very different history and traditions from the Western world. Philippe Le Corre and Alain Sepulchre examine how Europe's China presence can serve as a benchmark to other developed economies - especially the United States, which is also seeing a rise in Chinese investments.